A systems approach to scale-up for population health improvement - Harriet Koorts; Harry Rutter (BMC, 2021)
Abstract Despite a number of important global public health successes, for many health behaviours there is a continued lack of interventions that have been sufficiently scaled up to achieve system-wide integration. This has limited sustainable and equitable population health improvement. Systems change plays a major role in the relation between implementation processes and at-scale institutionalisation of public health interventions. However, in research, systems approaches remain underutilised in scaling up. Public health scale-up models have typically centred on intervention replication through linear expansion. In this paper, we discuss current conceptualisations and approaches used when scaling up in public health, and propose a new perspective on scaling that shifts attention away from the intervention to focus instead on achieving the desired population-level health outcomes. In our view, 'scaling up' exists on a continuum. At one end, effective scaling can involve a linear, intervention-orientated expansive approach that prioritises the spread of evidence-based interventions into existing systems in order to drive expansion in the application of that intervention. At the other end, we contend that scale-up can sit within a complex systems paradigm in which interventions are conceptualised as events in systems. In this case, implementation and scale-up activities should focus on generating changes within the system itself to achieve the desired outcome. This we refer to as 'systems-orientated scale-up' to achieving population health improvement, which can complement traditional approaches in relevant situations. We argue that for some health behaviours, our proposed approach towards scaling up could enhance intervention implementation, sustainability and population health impact.